THE ROLE OF MODERN PEDAGOGICAL TECHNOLOGIES IN TEACHING THE TOPICS "ATOM IN A MAGNETIC FIELD. ZEEMAN EFFECT. SELECTION RULE FOR SPECTRAL TRANSITIONS" FROM THE ATOMIC PHYSICS COURSE (SCIENCE TIME JOURNAL, 2026)
The article discusses the role of modern pedagogical technologies in teaching the 3rd year physics students of higher educational institutions in the effective use of modern pedagogical technologies and increasing the level of mastering new knowledge in the course of atomic physics, which includes the separation of the atomic energy levels into components-multiplicity as a result of theinteraction of the specific magnetic moment of the atom under the influence of an external magnetic field, the occurrence of normal and anomalous Zeeman effects as a result of spectral separations depending on the total mechanical moment of the atom, the Lande factor, and the Bohr magneton. Using the interaction of atoms with a magnetic field, it is possible to obtain information about the structural structure and spectral composition of substances